Development of the SAKOLA Application: An Android-Based Assessment System for Physical Education, Sports, and Health in Elementary Schools - Rizkiya, Ikhlas; Syamsuar, Syamsuar (International Journal of Educational Dynamics, 2024)
This study aims to develop the SAKOLA (School Administration System) application, an Android-based tool designed to enhance the assessment process in Physical Education, Sports, and Health learning in elementary schools. Employing the Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study systematically addressed existing challenges faced by teachers in conducting assessments. Observations in Padang City elementary schools revealed significant difficulties, including manual processes, inadequate facilities, and a lack of technological tools for recording, analyzing, and communicating learning outcomes. The School Administration System (SAKOLA) application was designed to address these issues by providing features such as automatic summarization of assessments, mobile accessibility, and user-friendly navigation. The results demonstrated that the application is highly valid, with expert evaluations yielding an average validity score of 82.86%, categorized as "very valid". Practicality testing further confirmed its usability, with scores consistently categorized as "very good" across individual, group, and field tests. The application also proved effective in improving assessment efficiency and user satisfaction. These findings establish the SAKOLA application as a valid, practical, and effective tool, offering a significant advancement in the management of learning assessments for Physical Education, Sports, and Health in elementary schools.